Influence of Preparation Conditions of Mixed-valence Co/ZSM-5 Zeolites on Their Adsorption and Catalytic Properties in CO Oxidation - Ludmila P. Oleksenko; Vitaly K. Yatsimirsky; Larisa V. Lutsenko (Adsorption Science & Technology)
The adsorption properties, thermal stability and catalytic activity in CO oxidation of Co 2+ , Co 3+ -containing ZSM-5 zeolite systems with different metal loadings were studied. Treatment in H 2 caused an increase in the activity of Co 2+ /ZSM-5 and Co 2+ –Co 3+ /ZSM-5 systems, but the activity of the Co 3+ /ZSM-5 system remained unchanged, demonstrating the very low reducibility of the [Co(NH 3 ) 6 ] 3+ ion when embedded in the zeolite framework. The catalytic activity changed in the order: Co 3+ /ZSM-5 < Co 2+ –Co 3+ /ZSM-5 < Co 2+ /ZSM-5. A correlation was established between the temperature necessary for the total decomposition of the cobalt salts introduced into the zeolite, the acidity, the coordination state of the Co ions and the catalytic activity of the cobalt-containing zeolites.